Coagulation-Floculation Process in Water Remediation - Ro'in, Nur Fadillatur (Universitas Nahdlatul Ulama Surabaya, 2024)
The importance of water treatment to maintain water quality for safe consumption and prevent environmental pollution. Coagulation flocculation is one of the simple and low-cost Point Of Use (POU) technologies in treating water and wastewater. The use of coagulation-flocculation methods in water treatment effective in separating suspended solids and colloids in wastewater and surface water. The coagulation-flocculation process allows four or one of the basic coagulation mechanisms to occur, including double-layer compression, charge neutralization, interparticle bridging, and sweep coagulation or sweep flocculation. Determining the success of the coagulation-flocculation process is based on several things such as the type of coagulant used, the amount of coagulant dose added, the pH of the water to be treated, the level of turbidity, the speed of stirring, and the temperature of the water.